Patenting Biotechnological Inventions in Europe - Peter Raspor; Saša Bavec (Food Technology and Biotechnology, 2002)
The patent system has been able to provide the protection for the achievements of different technologies and in that way it has supported further development and growth of the industry where those achievements were implemented. Modern technologies like information technology and biotechnology with genetic engineering that appeared in the 70s have overgrown the frames of the existing patent system because of their exponential development during the last thirty years. Industry that invests a huge amount of money in these technologies, especially in the field of biotechnology, where the results are very uncertain, has started to claim changes in the patent system.